Crucial Role of Anions on Arrangement of Cu2S Nanocrystal Superstructures. Issue 8 (27th January 2014) - Xiong, Yansong; Deng, Ke; Jia, Yuying; He, Liangcan; Chang, Lin; Zhi, Linjie; Tang, Zhiyong
<x xml:space="preserve">Abstract</x> Both of the arrays of Cu2S nanowires and the superlattices of Cu2S nanoparticles are obtained by the solventless thermolysis of copper thiolate in the presence of laurate. For the first time, the types of anions in the reaction system, which are generally neglected in previous studies, are found to determine the structure of the final assembly products. Furthermore, experimental results shows in the presence of Cl‐ ions, Cl‐ ions participate in the self‐assembly process and promote the formation of Cu2S nanowire arrays. Finally, the content of Cl‐ ions is gradually decreased with assembly reaction proceeding. Therefore, duiring the process, Cl‐ ions play a role of 'catassembly' in the formation of Cu2S nanocrystal superstructures.